Improvement in Propagation through Seed Pre-Treatment in Medicinally Important Plant Cowitch (Mucuna pruriens (L.) DC.) - Patade, Vikas Yadav; Singh, Nirbhay; Grover, Atul; Bala, Madhu (Indian Forester, 2025)
Cowitch (Mucuna pruriens (L.) DC.) is an important medicinal plant. Germination was found very poor and slow in a genotype of the seed propagated plant. Present study reports effect of scarification with concentrated (98% v/v) sulfuric acid for different durations (5, 10, 30, 60, 120 min) followed by water soaking for 24 h on seed germination and seedling establishment. Acid pre-treatment for 120 min resulted in significantly (P â‰¤ 0.05) higher seed germination (95.0%) than the control (27.5%), water soaked (27.5%), and the shorter acid treatments. Further, the rate of germination was significantly higher in the acid pre-treatment for 120 min (Timson's Index: 76.0) than the control (Timson's Index: 14.0) and the shorter acid treatments. The seedling establishment was also significantly improved in the acid treatment (92.0%) than the control (20.5%). The acid pre-treatment to the seeds did not cause any adverse effects on seedling vigor, morphology and reproductive growth of the plants. The present study thus suggests acid treatment for 120 min for higher and rapid seed germination for propagation of the medicinally important plant.